PENERAPAN AKAD MUDHARABAH MUTHLAQOH PADA TABUNGAN TARAWI SEBAGAI SARANAPENGUMPULAN DANA AMAL STUDI KASUS BMT NU CABANG GLENMORE - Asrof Dzahuri; Dimas Bagas Firdauzy; Munawir (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Abstract: This study aims to examine the implementation of the Mudharabah Muthlaqah contract in the Tarawi Savings Program as a mechanism for collecting charitable funds at BMT NU Glenmore Branch. The Tarawi Savings Program, also known as the Ukhrawi Savings Program, is a saving product based on the Mudharabah Muthlaqah contract that enables members to save while simultaneously engaging in charitable activities without reducing their principal balance. This research employs a qualitative method through field observations, interviews, and documentation analysis. The findings indicate that the management of the Tarawi Savings Program at BMT NU Glenmore has been carried out effectively, transparently, and in accordance with sharia principles. All collected funds are accurately recorded in the administrative system and managed to generate profit, which is subsequently distributed to the poor, orphans, and other social beneficiaries. The strategy for collecting charitable funds includes excellent customer service, a deposit pick-up system, and religious based approaches that encourage member participation. The profit-sharing system where 50% of the profit is allocated to social and charitable activities allows members to contribute sustainably to social welfare. Members are motivated to participate because of spiritual values, social concern, and the belief that saving through the Tarawi Savings Program brings both worldly and ukhrawi (spiritual) benefits. Overall, the Tarawi Savings Program serves as an innovative sharia-based financial service that successfully integrates economic and social functions, empowers the community, and strengthens public trust in BMT NU Glenmore.